Shine Bright Like a Diamond: New Light on an Old Polymeric Semiconductor. Issue 10 (29th January 2020) - Giusto, Paolo; Cruz, Daniel; Heil, Tobias; Arazoe, Hiroki; Lova, Paola; Aida, Takuzo; Comoretto, Davide; Patrini, Maddalena; Antonietti, Markus
Abstract: Brilliance usually refers to the light reflected by the facets of a gemstone such as diamond due to its high refractive index. Nowadays, high‐refractive‐index materials find application in many optical and photonic devices and are mostly of inorganic nature. However, these materials are usually obtained by toxic or expensive production processes. Herein, the synthesis of a thin‐film organic semiconductor, namely, polymeric carbon nitride, by thermal chemical vapor deposition is presented. Among polymers, this organic material combines the highest intrinsic refractive index reported so far with high transparency in the visible spectrum, even reaching the range of diamond. Eventually, the herein presented deposition of high quality thin films and their optical characteristics open the way for numerous new applications and devices in optics, photonics, and beyond based on organic materials. Abstract : High‐quality, homogeneous thin films of polymeric carbon nitride (pCN) are synthesized. The deposition method allows for the fabrication of pCN thin films in the nanometer range with tunable thickness, without constraints on the substrate shape. The optical properties of the pCN thin films are investigated, revealing that they possess a very high refractive index, even in the range of diamond.